Waking Ned Devine [videorecording (DVD)] - Jones, Kirk, 1964-; Bannen, Ian, 1928-1999; Kelly, David, 1929-2012; Flanagan, Fionnula, 1941- (Twentieth Century Fox Home Entertainment, 1999)
When Ned Devine dies from shock after winning the lottery, two longtime friends, Michael and Jackie, discover the body and agree Ned would want them to benefit from his good luck. They embark upon an outrageous scheme to claim the ticket -- but first they have to get all the townsfolk to go along with their plan.